Leadership Typology of Traditional Islamic Boarding School in Eastern Indonesia: Learning to Lead from DDI Mangkoso - Ismail Suardi Wekke; Ngesti Wihayuningtyas; Payiz Zawahir Muntaha; Mukhlis Mukhlis (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
This article aims to analyses the leadership style of Muslim priest (kyai) in traditional Islamic boarding school (pesantren) seeing from Weber’s leadership theory in managing human resources, infrastructure, finance, and social capital in the pesantren for development. This research also intends to review the existence of selected traditional Islamic boarding school with the types of what Weber’s explain in his article. Using library study in a qualitative approach in nature on several sources, i.e., library books, documents and information on the internet. DDI Mangkoso in South Sulawesi province was selected due to its long history as Islamic institution and their renowned and charismatic and transformative kyai since their early years of establishment. The analysis in this research somehow managed to reveal that the three Weber’s patterns type is found in the leadership of kyai in several pesantrens around Indonesia including in DDI Mangkoso. Traditional leadership of DDI Mangkoso’s kyai is strongly influenced by the tradition of education in pesantren which respects kyai’s position as the leader and the founder of the pesantren. However, charismatic and transformative leadership through Anregurutta K.H. Abdul Rahman Ambo Dalle and KH Farid Wajedi were the two most influence styles among Kyai in DDI Mangkoso until now